High-Performance Energy Selective Surface Based on the Double-Resonance Concept - Zhou, Lin; Liu, Liangliang; Shen, Zhongxiang (IEEE transactions on antennas and propagation, 2021)
In this article, a high-performance energy selective surface (ESS) is proposed based on a double-resonance concept, which has a nonlinear transmission response for high-power electromagnetic protection. With well-designed grid and cross patterns as well as properly chosen p-i-n diodes, bandpass and band-stop resonances are excited by the ESS at the same frequency under low and high incident power levels, respectively, resulting in low insertion loss (IL) and high shielding effectiveness (SE) of the ESS. Two samples of single-layer and double-layer ESSs operating at 3 GHz are designed to demonstrate the double-resonance concept. By utilizing a double-layer structure, a second-order band-stop resonance is produced to achieve a broader bandwidth with high SE in comparison with the single-layer ESS. Equivalent circuit models are employed to explain how the double resonances are produced and a wide bandwidth of high SE is obtained. Field circuit cosimulation is conducted to estimate the nonlinear performance of the ESS designs. Moreover, the ESS designs are measured in a rectangular waveguide setup. Good agreement is observed between the simulation and measurement. Simulated and measured results demonstrate that low IL less than 1 dB and high SE larger than 24 dB can be obtained under low and high incident power levels, respectively.